Cicli, emicicli e risonanze: “Call for Work 2012” (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
The paper deals with a detailed analysis of the awarded works presented at the international Call for Work (Design / Music), related to the conceptual and poetic sphere of Music and Architecture: Composition, Space, Symbol, for architects and musicians under 45, which followed the first Music and Architecture conference (18 October 2011). The awarded works are those of the German collective Eyland07 together with the artist Florian Tuercke and that of the Campanian composer Salvatore Carannante, both endowed with an ecological attitude, whose willingness to listen to what is other than itself, be the spaces and the sounds who inhabit the place with which the work will coexist, or the disciplines that contribute to its creation, favor a joint integration of knowledge. The German group awarded works are: Urban-audio / Eyland07, an interactive and participatory installation for a public space designed and built for the city of Tallin and hEAR TOuch LISTEN. The first work is based on a mobile sound object composed of 12 PVC pipes through which the sound is produced, picked up by a series of microphones connected to a mixer, to listen in the headphones the result of free acoustic explorations of the city. The second, conceived and created for the Bass Concert Hall in Austin / Texas, is based on the same principle as the previous one, but it is no longer the air that carries the sounds of the city through the pipes, but some of the same material components of the building that houses the installation is resonant. The work In the Temple of Mercury by Salvatore Carannante consists in the elaboration of the sound that is self-organizing directly in situ, in a space from which concretely and tangibly the resonances of the stones, the metals, the walls themselves emerge. As a whole, the exploration of the conceptual and poetic sphere of these works was an opportunity to reflect on the themes of creativity in the two disciplines, which have in common the same goal, that of “filling” time and space to “build” what before did not exist.